2017
DOI: 10.1016/j.vaccine.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of APC recruitment at the site of injection following injection of vaccine adjuvants

Abstract: a b s t r a c tVaccines often contain adjuvants to strengthen the response to the vaccine antigen. However, their modes of action at the site of injection (SOI) are poorly understood. Therefore, we assessed the local effects of adjuvant on the innate immune system in mice. We investigated the safe, widely used adjuvants MF59 and aluminum hydroxide (alum), as well as trehalose-6,60 -dibehenate (TDB), Complete Freund's Adjuvant (CFA) and the Toll-Like-Receptor-ligands lipopolysaccharide (LPS) and Pam3CysSerLys4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…MPL in AS02 may also activate the NF-κB signaling pathway (GO Enrichment “I-κB kinase/NF-κB signaling,” P -value 0.028, data not shown) through TLR-4 receptors on immune cells, such as macrophages or dendritic cells at the intramuscular injection site ( 52 ). Cytokines such as interleukin-1 can promote monocyte and immature DC recruitment to the injection-site, and mobilize these monocytes into APCs ( 53 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…MPL in AS02 may also activate the NF-κB signaling pathway (GO Enrichment “I-κB kinase/NF-κB signaling,” P -value 0.028, data not shown) through TLR-4 receptors on immune cells, such as macrophages or dendritic cells at the intramuscular injection site ( 52 ). Cytokines such as interleukin-1 can promote monocyte and immature DC recruitment to the injection-site, and mobilize these monocytes into APCs ( 53 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the mice vaccinated with LiChimera developed antigen-specific cellular and humoral immune responses, which were significantly enhanced when LiChimera was given along with Addavax, a commercial oil-in-water emulsion analogue of the MF59 adjuvant. The main effect of that emulsion was the effective recruitment of APCs to the site of injection followed by their migration to draining lymph nodes for antigens presentation to the CD4 + T cells [ 72 , 73 ]. Importantly, we found that bone marrow-derived macrophages from the LiChimera/Addavax-vaccinated mice presented enhanced leishmanicidal capacity as assessed by a decreased percentage of infected cells, which was attributed to increased levels of NO production.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental adjuvant CFA is known to induce strong inflammatory responses [33,36] including the induction of autoimmune arthritis in rats [37,38] and mice [39], and therefore not suitable for human vaccines [33]. It was included as the compound to secure maximal immune activation and indeed we were able to show that unrelated transferred CD4 + T cells were activated and proliferating after CFA prime injection as well as after CFA/IFA prime-boost injection (Fig 3) indicating bystander activation.…”
Section: Discussionmentioning
confidence: 99%